HUBUNGAN KARAKTERISTIK DAN PARTISIPASI MASYARAKAT PESERTA BANK SAMPAH - Sari Amalia; Danang Biyatmoko; Idiannor Mahyudin; Eko Rini Indrayatie (Universitas Lambung Mangkurat, 2021)
Kuala Kapuas potential waste is 30.5 tons/day or 11,133.41 tons/year where the amount of waste that utilized by Garbage Bank is only 0.6 tons/day. The participants of the Garbage Bank is 281 out of a total 61,005 Kuala Kapuas’ citizien. This research aims to analyze respondents' participation rate, analyze respondents' characteristics based on internal factors (gender, age, level of education, occupation, knowledge, perception) and external factors (role of government and facilities/infrastructure), and to analyze the correlation between community participation and internal and external factors. The research using quantitative approach. The population of this research is 218 participants of Garbage Bank. The research sample calculated using Slovin formula with 74 respondents with simple random sampling techniques. The research was conducted in Selat Dalam Sub-district, Kuala Kapuas. Research instruments used stuffing sheets and questionnaires. The data was tested using the chi square formula. The results showed the community participation in waste management was good, there are 49 respondents or 66.22% with high participation rate. The majority of participants’ gender is female with 52 respondents or 70.2%. The dominant age group was 36-45 years old with 30 respondents or 40.54%. The dominant level of education was the secondary level of 52 respondents or 70.27%. The dominant occupation was housewives with 38 respondents or 51.35%. There are 37 respondents or 50% with high level of knowledge and 49 respondents or 66.22% with good perception. 44 respondents or 59.46% considered that the role of government was moderate. 46 respondents or 62.16% of respondents considered a great level for infrastructure. There was a correlation between gender, knowledge, perception, role of government, facilities/infrastructure with the level of community participation. There was no correlation between age, education, and occupation factors with the level of community participation